Investigating EFL teachers’ perceptions on their TPACK development: how EFL teachers view seven domains on TPACK framework - Lailatun Nurul Aniq; Nur Arifah Drajati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
Despite the fact that plenteous studies on educational technology and strategic domain have been conducted, various studies indicated that EFL teachers do not explore the full potential of information and communication technology (ICT) in their classroom. It requires EFL teachers’ consideration to be able to intensify their knowledge, which emphasizes the understanding on how technology development nowadays may encourage the improvements of language learning, and it may change the professional teachers’ roles and practices. In order to help EFL teachers integrate modern technology into their EFL classroom, EFL teachers need to understand better the fundamental elements that may foster technology integration. Technological Pedagogical Content Knowledge (TPACK) is a framework for understanding the varied forms of knowledge necessitated by EFL teachers to integrate ICT in their teaching. This study aimed to investigate how EFL teachers’ perceptions of competences in their TPACK development. Hence, this study used a case study since it was an appropriate method in conducting the research. The data were collected from 20 EFL teachers by conducting online semi-structured interviews. The findings indicated that most EFL teachers rated their domain knowledge higher about CK, PK, and PCK rather than those domains concerned with technological knowledge, i.e., TK, TCK, TPK, and TPACK. The implication of this research is to add EFL teachers’ understanding of the importance of the TPACK framework. In the future, it takes part in developing the competence of EFL teachers’ TPACK development so that the quality of the teaching-learning process promotes.